Halogen-free flame-retardant fireproof cable material and preparation method thereof

By adding magnetic materials and bio-based plasticizers to the cable materials and undergoing plasma surface treatment, the problem of smoke and toxic gases generated during combustion of traditional cable materials is solved, significantly improving flame retardant performance and reducing environmental impact, providing a green solution.

CN119708666APending Publication Date: 2025-03-28STATE GRID HENAN ELECTRIC POWER CO FENGQIU COUNTY POWER SUPPLY CO
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411708829.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional cable materials produce a large amount of smoke and toxic gases when burned, and the flame retardant and environmental protection performance are insufficient, which poses safety hazards and environmental problems.

Method used

By innovatively adding magnetic materials and bio-based plasticizers and surface-treating magnetic materials with plasma, the flame retardant and fire-retardant performance of cable materials is significantly improved and the environmental impact is reduced.

Benefits of technology

It significantly improves the flame-retardant and fire-retardant performance of cable materials, reduces the production of smoke and toxic gases, and reduces the impact on the environment, providing a new green solution for the development of halogen-free flame-retardant and fire-retardant cable materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708666A_ABST
    Figure CN119708666A_ABST
Patent Text Reader

Abstract

The invention discloses a halogen-free flame-retardant fireproof cable material and a preparation method thereof, and relates to the technical field of cable materials, the material comprises the following components: 100 parts of polymer matrix resin, 50-80 parts of a halogen-free flame retardant, 5-15 parts of a magnetic material, 10-20 parts of a bio-based plasticizer, 1-3 parts of an antioxidant, and 1-3 parts of a lubricant. By adding the halogen-free flame retardant and the magnetic material subjected to specific treatment, the flame-retardant and fireproof performance of the cable material is remarkably improved, the additives can effectively absorb heat, inhibit flame spreading and reduce smoke and toxic gas in the combustion process, meanwhile, plasma is used for conducting surface treatment on the magnetic material, and the flame-retardant and fireproof performance of the cable material is improved. The compatibility and the interface bonding force between the magnetic material and other materials are enhanced, so that the flame retardant can be more uniformly dispersed in the cable material, and the flame-retardant effect is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable materials, in particular to a halogen-free flame-retardant and fireproof cable material and a preparation method thereof. Background Art

[0002] With the rapid development of modern society and the continuous advancement of science and technology, cable materials, as the basic components of power transmission and signal transmission, have increasingly higher performance requirements. Cable materials not only need to have good electrical properties and mechanical strength, but also must meet specific flame retardant, fireproof and environmental protection requirements. Especially in the fields of high-rise buildings, subways, aerospace, new energy, etc., more stringent standards are proposed for the flame retardant and fireproof properties of cable materials. Therefore, the research and development of high-performance and environmentally friendly cable materials has become an important research direction in the current field of cable materials.

[0003] Traditional cable materials often produce a lot of smoke and toxic gases during the combustion process, which not only poses a serious threat to the environment and human health, but also limits the application of cable materials in certain specific occasions. Although there are some flame-retardant cable materials on the market, they may still release harmful substances when burned, and the flame retardant properties of some materials are not ideal. In addition, the preparation process of traditional cable materials may involve the use of harmful chemicals, posing potential risks to the environment and the health of production workers.

[0004] In view of the problem that traditional cable materials produce a large amount of smoke and toxic gases when burned, as well as the deficiencies in flame retardant and environmental protection performance, although some improvements have been made in the existing technology, these improvement methods often ignore the overall performance and environmental protection requirements of the cable materials, resulting in certain safety hazards and environmental problems in practical applications. The present invention, by innovatively adding magnetic materials and bio-based plasticizers and using plasma to perform surface treatment on the magnetic materials, not only significantly improves the flame retardant and fireproof properties of the cable materials, but also reduces the impact on the environment, providing a new green solution for the development of halogen-free flame retardant and fireproof cable materials. Summary of the invention

[0005] The purpose of the present invention is to make up for the deficiencies of the prior art and to provide a halogen-free flame retardant and fireproof cable material and a preparation method thereof. The material can be innovatively added with magnetic materials and bio-based plasticizers and surface treated with plasma to significantly improve the compatibility and interfacial bonding between materials and significantly enhance the flame retardant and fireproof properties of the cable material. At the same time, due to the use of bio-based plasticizers and environmentally friendly halogen-free flame retardants, the present invention reduces the impact on the environment while also providing a new green solution for the development of halogen-free flame retardant and fireproof cable materials.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: on the one hand, a halogen-free flame retardant and fireproof cable material, which includes the following components: 100 parts of polymer matrix resin, 50-80 parts of halogen-free flame retardant, 5-15 parts of magnetic material, 10-20 parts of bio-based plasticizer, 1-3 parts of antioxidant, and 1-3 parts of lubricant.

[0007] Furthermore, the polymer matrix resin is one or more of polyethylene, polypropylene, polyvinyl chloride, and polystyrene, and is dried by placing it in an oven at a temperature of 80-100° C. for 2-4 hours to remove moisture absorbed by the polymer matrix resin during storage and transportation.

[0008] Furthermore, the halogen-free flame retardant is one or more of magnesium hydroxide, aluminum hydroxide, red phosphorus, and melamine phosphate, and is subjected to surface modification treatment when used. Specifically, a silane coupling agent is used for surface treatment, the silane coupling agent is dissolved in ethanol or water to prepare a solution with a concentration of 1-3%, and the halogen-free flame retardant is added to the solution, the ratio of the flame retardant to the solution is 1:3-5, and the solution is heated to 50-70°C while stirring, and the reaction time is 2-4 hours. After the reaction is completed, the flame retardant is filtered, washed with deionized water for multiple times, and dried in an oven at 80-100°C for 4-6 hours.

[0009] Furthermore, the magnetic material is one or more of ferroferric oxide, ferrite, and neodymium iron boron, and is subjected to plasma treatment and magnetic field pretreatment when used. For plasma treatment: the magnetic material is placed in a plasma treatment device, argon is used as a plasma gas, the gas flow rate is 10-30sccm, the power is 50-150W, and the treatment time is 10-30 minutes, thereby changing the chemical properties and physical structure of the surface of the magnetic material. For magnetic field pretreatment: the plasma-treated magnetic material is placed in a magnetic field of a specific strength and direction, the magnetic field strength is between 0.5-2T, and the treatment time is 30-60 minutes, so that the magnetic material has a magnetic orientation, thereby guiding the distribution of the flame retardant in the cable material and promoting the orderly formation of the carbon layer.

[0010] Furthermore, the bio-based plasticizer is one or more of epoxidized soybean oil, tributyl citrate, and acetyl tributyl citrate.

[0011] Furthermore, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168, and the lubricant is one or more of stearic acid, calcium stearate, and zinc stearate, wherein the ratio of the antioxidant to the lubricant is 2:1.

[0012] On the other hand, a method for preparing a halogen-free flame-retardant fireproof cable is characterized in that the method comprises the following specific steps: Antioxidant premix: premix the antioxidant and lubricant in a ratio of 2:1; The raw materials are mixed to obtain a premix: 100 parts of the pretreated polymer matrix resin, 50-80 parts of the halogen-free flame retardant, 5-15 parts of the magnetic material, 10-20 parts of the bio-based plasticizer, and 2-5 parts of the premixed antioxidant and lubricant are added into a high-speed mixer, and the mixer parameters are adjusted to make the raw materials fully mixed to obtain a premix; Melt extrusion: Add the premix into a twin-screw extruder for melt extrusion. Adjust the extruder parameters, including extrusion temperature and screw speed. During the extrusion process, the premix gradually melts under the shearing and heating of the screw and is extruded into continuous strips at the die head of the extruder. Cooling and pelletizing: The extruded material is cooled through a cooling water trough, cut into pellets of a certain length through a pelletizer, and the obtained halogen-free flame-retardant and fire-proof cable material pellets are packaged and stored.

[0013] Furthermore, in the step of mixing the raw materials to obtain the premix, the mixer parameters are adjusted to allow the raw materials to be fully mixed and uniformly to obtain the premix, wherein the mixer parameters are adjusted to: mixing speed 1500-2500rpm, mixing time 15-30 minutes.

[0014] Furthermore, in the melt extrusion step, the extrusion temperature is between 150-200° C. and the screw speed is 100-300 r / min.

[0015] Furthermore, in the cooling and pelletizing step, the cooling water temperature is controlled between 20-30° C., and the pelletizing length is 2-5 mm.

[0016] Compared with the prior art, the halogen-free flame-retardant and fire-proof cable material and its preparation method have the following beneficial effects: 1. The present invention significantly improves the flame retardant and fireproof properties of cable materials by adding halogen-free flame retardants and specially treated magnetic materials. These additives can effectively absorb heat, inhibit the spread of flames, and reduce the generation of smoke and toxic gases during the combustion process. At the same time, the magnetic material is surface treated with plasma to enhance the compatibility and interface bonding force between the magnetic material and other materials, so that the flame retardant can be more evenly dispersed in the cable material, further improving the flame retardant effect.

[0017] 2. The present invention effectively improves the flame retardant properties of cable materials by scientifically proportioning halogen-free flame retardants and polymer matrix resins. Halogen-free flame retardants can absorb heat, release moisture or produce non-combustible gases during combustion, thereby slowing down the spread of fire and reducing combustion intensity. At the same time, the addition of magnetic materials and their surface treatment and magnetic field pretreatment further enhance the thermal stability and flame retardancy of the materials, so that the cable materials can better maintain structural integrity when encountering fire, reducing the damage of fire to the cables and their transmission systems.

[0018] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 The present invention is a flow chart of a method for preparing a halogen-free flame-retardant and fire-proof cable material. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Embodiment 1

[0022] The present embodiment focuses on a method for preparing a halogen-free flame-retardant fireproof cable material. The polymer matrix resin is 100 parts of polyethylene, the halogen-free flame retardant is composed of 50 parts of magnesium hydroxide and 15 parts of red phosphorus, the magnetic material is composed of 5 parts of ferroferric oxide, 2 parts of ferrite and 1 part of neodymium iron boron, the bio-based plasticizer is 12 parts by weight of epoxy soybean oil, the antioxidant is composed of 1.5 parts of antioxidant 1010 and 0.5 parts of antioxidant 168, and the lubricant is 1.5 parts of calcium stearate. First, the polyethylene is dried in an oven at 85°C for 3 hours to remove any moisture that may be absorbed and prevent bubbles or degradation during processing. Surface modification of magnesium hydroxide and red phosphorus: For magnesium hydroxide, a silane coupling agent is used for surface treatment. The silane coupling agent is dissolved in ethanol to prepare a solution with a concentration of 2%. Magnesium hydroxide is added to the solution. The mass ratio of magnesium hydroxide to the solution is 1:4. While stirring, the solution is heated to 60°C. The reaction time is 3 hours. After the reaction is completed, the magnesium hydroxide is filtered and washed with deionized water for several times. Finally, it is dried in an oven at 90°C for 5 hours. For red phosphorus, stearic acid is used for surface treatment. The stearic acid is heated to 70°C to melt it. Then, red phosphorus is added to the stearic acid. The mass ratio of red phosphorus to stearic acid is 1:0.3. Stir and keep The temperature is maintained at 70°C for 2 hours. After the reaction is completed, the reaction is cooled to room temperature, the red phosphorus is filtered and dried, and then the ferroferric oxide, ferrite and neodymium iron boron are subjected to plasma treatment and magnetic field pretreatment: For plasma treatment: the magnetic material is placed in a plasma treatment device, argon is used as the plasma gas, the gas flow rate is 20sccm, the power is 100W, and the treatment time is 20 minutes. Plasma treatment can change the chemical properties and physical structure of the surface of the magnetic material, and improve its compatibility and interface bonding force with other materials. For magnetic field pretreatment: the magnetic material treated with plasma is placed in a magnetic field with a magnetic field strength of 1T. The treatment time is 45 minutes. The magnetic field pretreatment can make the magnetic material have a certain magnetic property orientation, so that it can play a better role in the cable material. The epoxidized soybean oil is then filtered: the epoxidized soybean oil is filtered using a microporous filter membrane with a pore size of 0.3μm to remove possible impurities therein. Finally, the antioxidant 1010, antioxidant 168 and calcium stearate are premixed: 1.5 parts of antioxidant 1010, 0.5 parts of antioxidant 168 and 1.5 parts of calcium stearate are added to a small high-speed mixer, and the high-speed mixer is started with a mixing speed of 1500rpm and a mixing time of 8 minutes to fully mix the antioxidant and lubricant to obtain a premix.

[0023] 100 parts of pretreated polyethylene, 50 parts of magnesium hydroxide, 15 parts of red phosphorus, 5 parts of ferrosoferric oxide, 2 parts of ferrite, 1 part of neodymium iron boron, 12 parts of epoxy soybean oil and a premix of an antioxidant and a lubricant are added to a high-speed mixer, the high-speed mixer is started, the mixing speed is 2000rpm, the mixing time is 20 minutes, the raw materials are fully mixed and uniform, and a premix is ​​obtained, the premix is ​​added to a twin-screw extruder for melt extrusion, the extrusion temperature is set to 180°C, the screw speed is 200r / min, during the extrusion process, the premix is ​​gradually melted under the shearing and heating action of the screw, and is extruded into a continuous strip material at the die head of the extruder, the extruded material is cooled by a cooling water tank, the cooling water temperature is controlled at 25°C, the cooled material becomes hard, and then it is cut into granules with a length of 3mm by a pelletizer, finally, the obtained halogen-free flame retardant and fireproof cable material particles are packaged and stored, in this embodiment, due to the low proportion of magnetic material, the enhanced performance of flame retardancy is small. Embodiment 2

[0024] The present embodiment further optimizes the preparation method of halogen-free flame retardant fireproof cable material. The polymer matrix resin is polyethylene, which is 100 parts by weight. The halogen-free flame retardant is composed of 50 parts of magnesium hydroxide and 15 parts of red phosphorus. The magnetic material is composed of 8 parts of ferroferric oxide, 3 parts of ferrite, and 2 parts of neodymium iron boron. The bio-based plasticizer is epoxy soybean oil, which is 12 parts by weight. The antioxidant is composed of 1.5 parts of antioxidant 1010 and 0.5 parts of antioxidant 168. The lubricant is calcium stearate, which is 1.0 parts by weight. The polyethylene was first dried in an oven at 85°C for 3 hours to remove moisture. The surface of the halogen-free flame retardant was modified as follows: for the surface treatment of magnesium hydroxide, a silane coupling agent was used for surface treatment. The silane coupling agent was dissolved in ethanol to prepare a 2% solution. Magnesium hydroxide was added to the solution at a mass ratio of 1:4. The solution was stirred and heated to 60°C for 3 hours. After filtering, it was washed with deionized water and dried in an oven at 90°C. Dry for 5 hours, for red phosphorus surface treatment: surface treatment with stearic acid, heat stearic acid to 70°C to melt, add red phosphorus, mass ratio of 1:0.3, stir and maintain 70°C, react for 2 hours, filter and dry after cooling, and then treat the magnetic material: for plasma treatment: put ferrosoferric oxide, ferrite and neodymium iron boron into a plasma treatment equipment, use argon as plasma gas, gas flow rate 20sccm, power 100W, treatment time 20 minutes, for magnetic field pretreatment: the treated magnetic material is placed in a magnetic field with a magnetic field strength of 1T, the treatment time is 45 minutes, followed by epoxy soybean oil filtration treatment: filter the epoxy soybean oil with a microporous filter membrane with a pore size of 0.3μm to remove impurities, and finally premix the antioxidant and lubricant: add 1.5 parts of antioxidant 1010, 0.5 parts of antioxidant 168 and 1.5 parts of calcium stearate to a small high-speed mixer and mix at a speed of 1500rpm for 8 minutes to obtain a premix.

[0025] 100 parts of pretreated polyethylene, 50 parts of magnesium hydroxide, 15 parts of red phosphorus, 8 parts of ferrosoferric oxide, 3 parts of ferrite, 2 parts of neodymium iron boron, 12 parts of epoxy soybean oil and a premix of an antioxidant and a lubricant are added to a high-speed mixer and mixed at a speed of 2000 rpm for 20 minutes to fully mix the raw materials to obtain a premix. The premix is ​​added to a twin-screw extruder for melt extrusion. The extrusion temperature is set to 180°C and the screw speed is 200r / min. The premix is ​​gradually melted under the shearing and heating action of the screw and extruded into a continuous strip material at the die head. The extruded material is cooled by a cooling water tank with the water temperature controlled at 25°C. The cooled material hardens and is cut into 3 mm long particles by a pelletizer. Finally, the halogen-free flame retardant and fireproof cable material particles are packaged and stored. In this embodiment, the increase in the proportion of magnetic material further enhances the flame retardant properties of the cable material, the guiding effect of the magnetic field on the flame retardant is more obvious, and the formation of the carbon layer is more orderly. Embodiment 3

[0026] The present embodiment aims to describe in detail a halogen-free flame-retardant fireproof cable material and a preparation method thereof. The polymer matrix resin is polyethylene, which is 100 parts by weight. The halogen-free flame retardant is composed of 50 parts of magnesium hydroxide and 15 parts of red phosphorus. The magnetic material is composed of 10 parts of ferroferric oxide, 4 parts of ferrite, and 3 parts of neodymium iron boron. The bio-based plasticizer is epoxy soybean oil, which is 12 parts by weight. The antioxidant is composed of 1.5 parts of antioxidant 1010 and 0.5 parts of antioxidant 168. The lubricant is calcium stearate. , 1.5 parts by weight, first dry the polyethylene: put the polyethylene in an oven at 85°C and dry it for 3 hours, then modify the surface of the halogen-free flame retardant: for the surface treatment of magnesium hydroxide: use a silane coupling agent for surface treatment, dissolve the silane coupling agent in ethanol, prepare a solution with a concentration of 2%, add magnesium hydroxide to the solution, the mass ratio is 1:4, stir and heat to 60°C, react for 3 hours, filter and wash with deionized water, and dry in an oven at 90°C 5 hours, for red phosphorus surface treatment: surface treatment with stearic acid, heat the stearic acid to 70°C to melt, add red phosphorus, the mass ratio is 1:0.3, stir and maintain 70°C, react for 2 hours, filter and dry after cooling, and then treat the magnetic material: for plasma treatment: put ferroferric oxide, ferrite and neodymium iron boron into a plasma treatment equipment, use argon as plasma gas, gas flow rate 20sccm, power 100W, treatment time 20 minutes, for magnetic field pretreatment: the treated magnetic material is placed in a magnetic field with a magnetic field strength of 1T, the treatment time is 45 minutes, followed by epoxy soybean oil filtration treatment: filter the epoxy soybean oil with a microporous filter membrane with a pore size of 0.3μm to remove impurities, and finally pre-mix the antioxidant and lubricant: add 1.5 parts of antioxidant 1010, 0.5 parts of antioxidant 168 and 1.5 parts of calcium stearate into a small high-speed mixer, mix at a speed of 1500rpm for 8 minutes to obtain a premix.

[0027] 100 parts of pretreated polyethylene, 50 parts of magnesium hydroxide, 15 parts of red phosphorus, 10 parts of ferroferric oxide, 4 parts of ferrite, 3 parts of neodymium iron boron, 12 parts of epoxy soybean oil, and a premix of an antioxidant and a lubricant are added to a high-speed mixer and mixed at a speed of 2000 rpm for 20 minutes to fully mix the raw materials to obtain a premix. The premix is ​​added to a twin-screw extruder for melt extrusion. The extrusion temperature is set to 180°C and the screw speed is 200r / min. The premix is ​​gradually melted under the shearing and heating action of the screw and extruded into a continuous strip material at the die head. The extruded material is cooled by a cooling water tank, and the water temperature is controlled at 25°C. The cooled material hardens and is cut into 3 mm long particles by a pelletizer. Finally, the halogen-free flame retardant and fireproof cable material particles are packaged and stored. In this embodiment, the proportion of magnetic material is further increased, the flame retardant performance of the cable material is significantly improved, and the density and stability of the carbon layer under the action of the magnetic field are further enhanced, which is suitable for cable application scenarios with high requirements for flame retardant performance. Embodiment 4

[0028] This embodiment optimizes a method for preparing a halogen-free flame-retardant fireproof cable material. The polymer matrix resin is polyethylene, which is 100 parts by weight. The halogen-free flame retardant is composed of 50 parts of magnesium hydroxide and 15 parts of red phosphorus. The magnetic material is composed of 12 parts of ferroferric oxide, 5 parts of ferrite, and 4 parts of neodymium iron boron. The bio-based plasticizer is epoxy soybean oil, which is 12 parts by weight. The antioxidant is composed of 1.5 parts of antioxidant 1010 and 0.5 parts of antioxidant 168. The lubricant is calcium stearate, which is 1.5 parts by weight. First, the polyethylene is dried: the polyethylene is placed in an oven at 85°C and dried. Dry for 3 hours to remove the moisture that may be absorbed. Secondly, modify the surface of the halogen-free flame retardant. For the surface treatment of magnesium hydroxide: use silane coupling agent for surface treatment. Dissolve the silane coupling agent in ethanol to prepare a solution with a concentration of 2%. Then, add magnesium hydroxide to the solution. The mass ratio of magnesium hydroxide to the solution is 1:4. While stirring, heat the solution to 60°C. The reaction time is 3 hours. After the reaction is completed, filter the magnesium hydroxide and wash it with deionized water for several times. Finally, dry it in an oven at 90°C for 5 hours. For the surface treatment of red phosphorus: use stearic acid for surface treatment. Heat stearic acid to 70°C to melt it, add red phosphorus to stearic acid, the mass ratio of red phosphorus to stearic acid is 1:0.3, keep the temperature at 70°C under stirring, the reaction time is 2 hours, after the reaction is completed, cool to room temperature, filter the red phosphorus and dry it, and then treat the magnetic material: For plasma treatment: put ferroferric oxide, ferrite and neodymium iron boron into a plasma treatment equipment, use argon as plasma gas, the gas flow rate is 20sccm, the power is 100W, and the treatment time is 20 minutes. For magnetic field pretreatment: put the magnetic material treated with plasma The material is placed in a magnetic field with a magnetic field strength of 1 T for 45 minutes, and then the epoxidized soybean oil is filtered: the epoxidized soybean oil is filtered using a microporous filter membrane with a pore size of 0.3 μm to remove impurities therein, and finally the antioxidant 1010, antioxidant 168 and calcium stearate are premixed: 1.5 parts of antioxidant 1010, 0.5 parts of antioxidant 168 and 1.5 parts of calcium stearate are added to a small high-speed mixer, and the high-speed mixer is started at a mixing speed of 1500 rpm for 8 minutes to fully mix the antioxidant and the lubricant to obtain a premix.

[0029] 100 parts of pretreated polyethylene, 50 parts of magnesium hydroxide, 15 parts of red phosphorus, 12 parts of ferroferric oxide, 5 parts of ferrite, 4 parts of neodymium iron boron, 12 parts of epoxidized soybean oil, and a premix of an antioxidant and a lubricant are added to a high-speed mixer, and the high-speed mixer is started at a mixing speed of 2000 rpm for 20 minutes to fully mix the raw materials to obtain a premix, and the premix is ​​added to a twin-screw extruder for melt extrusion, the extrusion temperature is set to 180°C, the screw speed is 200 r / min, and during the extrusion process, the premix is ​​sheared by the screw. The material is gradually melted under the action of heating and extruded into continuous strip materials at the die head of the extruder. The extruded material is cooled by a cooling water trough, and the cooling water temperature is controlled at 25°C. The cooled material becomes hard and is then cut into granules with a length of 3 mm by a pelletizer. Finally, the obtained halogen-free flame retardant and fireproof cable material particles are packaged and stored. In this embodiment, a higher proportion of magnetic material makes the cable material perform better in flame retardancy, and the guiding effect of the flame retardant at the key position when a fire occurs is more prominent, and the barrier effect of the carbon layer will also be better.

[0030] In summary, the halogen-free flame retardant and fireproof cable material of the present invention provides a new solution for improving the performance of cable materials by innovatively adding magnetic materials and bio-based plasticizers. During the preparation process, various materials are pretreated, including drying of the polymer matrix resin, surface modification of the halogen-free flame retardant, plasma treatment and magnetic field pretreatment of the magnetic material, filtering of the bio-based plasticizer, and premixing of the antioxidant and the lubricant. These pretreatment steps improve the compatibility and interfacial bonding between the materials, thereby improving the performance of the cable material. By adjusting the proportion of the magnetic material, different effects are presented in different embodiments. With the increase of the proportion of the magnetic material, the flame retardant properties of the cable material are significantly improved, the guiding effect of the magnetic field on the flame retardant is more obvious, and the formation of the carbon layer is more orderly, and the density and stability are enhanced.

[0031] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A halogen-free flame retardant fireproof cable material, characterized in that: The material comprises the following components: 100 parts of polymer matrix resin, 50-80 parts of halogen-free flame retardant, 5-15 parts of magnetic material, 10-20 parts of bio-based plasticizer, 1-3 parts of antioxidant and 1-3 parts of lubricant.

2. The halogen-free flame-retardant and fire-proof cable material according to claim 1, characterized in that: The polymer matrix resin is one or more of polyethylene, polypropylene, polyvinyl chloride, and polystyrene, and is dried by placing it in an oven at a temperature of 80-100° C. for 2-4 hours to remove moisture absorbed by the polymer matrix resin during storage and transportation.

3. The halogen-free flame-retardant and fire-proof cable material according to claim 1, characterized in that: The halogen-free flame retardant is one or more of magnesium hydroxide, aluminum hydroxide, red phosphorus, and melamine phosphate, and is subjected to surface modification treatment when used. Specifically, a silane coupling agent is used for surface treatment, the silane coupling agent is dissolved in ethanol or water to prepare a solution with a concentration of 1-3%, the halogen-free flame retardant is added to the solution, the ratio of the flame retardant to the solution is 1:3-5, the solution is heated to 50-70°C while stirring, the reaction time is 2-4 hours, after the reaction is completed, the flame retardant is filtered, washed with deionized water for multiple times, and dried in an oven at 80-100°C for 4-6 hours.

4. The halogen-free flame retardant and fireproof cable material according to claim 1, characterized in that: The magnetic material is one or more of ferroferric oxide, ferrite, and neodymium iron boron, and is subjected to plasma treatment and magnetic field pretreatment when used. For plasma treatment, the magnetic material is placed in a plasma treatment device, argon is used as plasma gas, the gas flow rate is 10-30sccm, the power is 50-150W, and the treatment time is 10-30 minutes, so as to change the chemical properties and physical structure of the surface of the magnetic material. For magnetic field pretreatment, the magnetic material treated with plasma is placed in a magnetic field with a specific strength and direction, the magnetic field strength is between 0.5-2T, and the treatment time is 30-60 minutes, so that the magnetic material has magnetic property orientation, thereby guiding the distribution of flame retardants in cable materials and promoting the orderly formation of carbon layers.

5. The halogen-free flame-retardant and fire-proof cable material according to claim 1, characterized in that: The bio-based plasticizer is one or more of epoxidized soybean oil, tributyl citrate, and acetyl tributyl citrate.

6. The halogen-free flame retardant and fireproof cable material according to claim 1, characterized in that: The antioxidant is a mixture of antioxidant 1010 and antioxidant 168, and the lubricant is one or more of stearic acid, calcium stearate, and zinc stearate, wherein the ratio of the antioxidant to the lubricant is 2:

1.

7. A method for preparing a halogen-free flame-retardant and fireproof cable according to any one of claims 1 to 6, characterized in that: The method comprises the following specific steps: Antioxidant premix: premix the antioxidant and lubricant in a ratio of 2:1; The raw materials are mixed to obtain a premix: 100 parts of the pretreated polymer matrix resin, 50-80 parts of the halogen-free flame retardant, 5-15 parts of the magnetic material, 10-20 parts of the bio-based plasticizer, and 2-5 parts of the premixed antioxidant and lubricant are added into a high-speed mixer, and the mixer parameters are adjusted to make the raw materials fully mixed to obtain a premix; Melt extrusion: Add the premix into a twin-screw extruder for melt extrusion. Adjust the extruder parameters, including extrusion temperature and screw speed. During the extrusion process, the premix gradually melts under the shearing and heating of the screw and is extruded into continuous strips at the die head of the extruder. Cooling and pelletizing: The extruded material is cooled through a cooling water trough, cut into pellets of a certain length through a pelletizer, and the obtained halogen-free flame-retardant and fire-proof cable material pellets are packaged and stored.

8. The method for preparing a halogen-free flame-retardant and fireproof cable according to claim 7, characterized in that: In the step of mixing the raw materials to obtain the premix, the mixer parameters are adjusted to make the raw materials fully and evenly mixed to obtain the premix, wherein the mixer parameters are adjusted as follows: mixing speed 1500-2500 rpm, mixing time 15-30 minutes.

9. The method for preparing a halogen-free flame-retardant and fireproof cable according to claim 7, characterized in that: In the melt extrusion step, the extrusion temperature is between 150-200° C. and the screw speed is 100-300 r / min.

10. The method for preparing a halogen-free flame-retardant and fireproof cable according to claim 7, characterized in that: In the cooling and pelletizing step, the cooling water temperature is controlled between 20-30° C., and the pelletizing length is 2-5 mm.

Citation Information

Cited By

  • Voltage breakdown resistant high-insulation EPDM material and application thereof

    CN120829650A